Metasintesis Terhadap Pola Reformasi Birokrasi Di Negar Negara Asean - PratiwiÂ , PratiwiÂ (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2014)
Forecast about the prospects of equitable economic development in ASEAN seems to be slow to materialize. lnequality in economic and governance atmosphere are dominant obstacles. However, the last two decades, countries with highest GDPper-aapita in ASEAN did a lot of reforms in the field of Government. This research was conducted to understand patterns, influencing factors, priority programmes and the implications of bureaucracy reform in those countries. This metasyntesis method from previous research concludes that pattem of bureaucratic reform and implications on those ASEAN countries are diï¬erent according to the intervention of the Government in the public services and the economy. Strong leadership, a clear reform vision, as well as a strong internal and external support are the four factors that aï¬ï¬ct bureaucratic reform in those five ASEAN countries.